FROM THE HISTORY OF THE STUDY OF MULTILINGUALISM AMONG QUMZARI SPEAKERS IN THE PERSIAN GULF - E.K. Molchanova (Многоязычие в образовательном пространстве, 2023)
The article deals with the small Iranian language Kumzari; its speakers live in the Persian Gulf region. This language has been heavily influenced by the Arabic language. The paper’s goal lies in critical analysis of the existing publications concerning Kumzari. The author presents a brief review of recent papers (published in the 21 century) by Canadian-European researchers E. and C. Anonby. The author considers and evaluates their views on the status, morphology and syntax of the Kumzari language. The conclusion is made that some of the researchers’ views are not justified and the discussed language needs a complex study by professional specialists in the Iranian and Arabic languages.